USLOVNI OTPUST KOD KAZNE DOŽIVOTNOG ZATVORA – KRITIČKO PREISPITIVANJE NOVIH NORMATIVNIH REŠENJA U SRPSKOM KRIVIČNOM ZAKONODAVSTVU – - Zdravko Grujić (Revija za kriminologiju i krivično pravo)
The amendments and supplements of the Criminal Code of 2019 introduced into Serbian criminal legislation a life imprisonment as the most severe sentence in the criminal sanctions system. These novelties confirm the continuity of a multi-year process of (inconsistent) changes in criminal legislation that tightens the legislature’s criminal policy, broadens the limits of criminal repression, supplements the purpose of punishment, narrows the possibility of mitigating the punishment, in other words, continues to expand the retributive concept of punishing. The introduction of the life imprisonment required the amendments of several other provisions of the Criminal Code, including those relating to the purpose of punishment, impossibility of conditional release of persons sentenced to this life imprisonment, as well as the duration limit on conditional release. In most states where it forms part of the sentence system the possibility of (early, or) conditional release of prisoners is provided. It is indisputable that there are also rare exceptions to this rule. However, the paradigm of human rights protection, in particular the protection of the rights of persons deprived of their liberty, as well as the mechanisms for their protection (e.g. the jurisprudence of the ECHR), indicate that the possibility of conditional release of persons sentenced to life imprisonment in national legislations already represents an “established standard”. From a penological point of view, the implementation of treatment and treating of the prisoners sentenced to life imprisonment and the idea of their resocialization and social reintegration, is directly correlated with the possibility of their conditional release. Therefore, prescribing the possibility of conditional release of prisoners sentenced to life imprisonment, as visible to them “a path to release”, is a necessary prerequisite for the execution of the sentence.